"Negotiating styles, a comparative perceptive" - shamssadat zahedi (مطالعات مدیریت بهبود و تحول, 1996)
Negotiating is the process of communicating back and forth for the purpose of reaching a joint agreement about differing needs or ideas. For successful negotiations, both parties should come to the negotiating table with having done some serious thinking about the barriers to and complexities of cross- cultural communications. There are four phases in negotiations: relationship building, information exchange, persuasion, and agreement. Beneath cultural differences in negotiation norms, are differences in underlying values and philosophies about the negotiation process. Among different strategies of negotiations: win-win, win-lose, and lose-lose, the first strategy is the best because it will help both sides to get benefit out of negotiation process.